Optimized Direct Padé and HPM for Solving Equation of Oxygen Diffusion in a Spherical Cell. (2nd September 2018) - Sandoval-Hernandez, M. A.; Vazquez-Leal, H.; Sarmiento-Reyes, A.; Filobello-Nino, U.; Castro-Gonzalez, F.; Herrera-May, A. L.; Callejas-Molina, R. A.; Ruiz-Gomez, R.
Abstract : This work presents the application of homotopy perturbation method (HPM) and Optimized Direct Padé (ODP) to obtain a handy and easily computable approximate solution of the nonlinear differential equation to model the oxygen diffusion in a spherical cell with nonlinear oxygen uptake kinetics. On one hand, the obtained HPM solution is fully symbolic in terms of the coefficients of the equation, allowing us to use the same solution for different values of the maximum reaction rate, the Michaelis constant, and the permeability of the cell membrane. On the other hand, the numerical experiments show the high accuracy of the proposed ODP solution, resulting in3.58 × 1 0 - 4 as the lowest absolute relative error (A.R.E.) for a set of coefficients. In addition, a novel technique is proposed to reduce the number of algebraic operations during the process of application of ODP method through the use of the Taylor series, which help to simplify the algebraic expressions used. The powerful process to obtain the solution shows that the Optimized Direct Padé and homotopy perturbation method are suitable methods to use.